A TAM-Based Analysis of Perceived Factors Influencing Satisfaction and Continued Use of MyBCA Mobile Banking - Duta Amay; Maria Apsari Sugiat (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the factors that affect the use of myBCA mobile banking among BCA customers. The research model used in this study is the Technology Acceptance Model (TAM) with an expansion of the model by adding the perceived security variable in mobile banking customers, which examines the extent to which the construction of perceived usefulness, perceived ease of use, as a utilitarian aspect and perceived enjoyment as a hedonic aspect, affects satisfaction and continuance intention to use BCA's mobile banking. This study uses a quantitative approach with purporsive sampling using the slovin formula with a total of 400 samples. The data was analyzed using Partial Least Square (PLS) and Structural Equation Modelling (SEM) with SmartPLS data processing tools. The results of this study show that the perceived usefulness variable has no effect on user satisfaction but has a significant positive effect on continuance intention to use. The perceived ease of use variable has a significant positive effect on perceived usefulness, user satisfaction, and perceived enjoyment. The perceived enjoyment variable and the perceived security variable had a significant positive effect on user satisfaction but had no effect on continuance intention to use. The user satisfaction variable has been shown to have a significant positive effect on continuance intention to use.